Younger than ever?: Subjective age is becoming younger and remains more stable in middle-age and older adults today - Wettstein, Markus; Wahl, Hans-Werner; Drewelies, Johanna; Wurm, Susanne; Huxhold, Oliver; Ram, Nilam; Gerstorf, Denis (Psychological science, 2023)
Little is known about historical shifts in subjective age (i.e., how old individuals feel). Moving beyond the very few time-lagged cross-sectional cohort comparisons, we examined historical shifts in within-person trajectories of subjective age from midlife to advanced old age. We used cohort-comparative longitudinal data from middle-age and older adults in the German Ageing Survey (N = 14,928; ~50% female) who lived in Germany and were between 40 and 85 years old when entering the study. They provided up to seven observations over 24 years. Results revealed that being born later in historical time is associated with feeling younger by 2% every birth-year decade and with less intraindividual change toward an older subjective age. Women reported feeling younger than men; this gender gap widened across cohorts. The association of higher education with younger subjective age became weaker across cohorts. Potential reasons for the subjective-rejuvenation effect across cohorts are discussed.
Online veröffentlicht: 18. April 2023